2021
DOI: 10.3390/pharmaceutics13101642
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Nanoparticles in Drug Delivery: Physicochemistry and Applications

Abstract: Hydroxyapatite (HAP) has been the gold standard in the biomedical field due to its composition and similarity to human bone. Properties such as shape, size, morphology, and ionic substitution can be tailored through the use of different synthesis techniques and compounds. Regardless of the ability to determine its physicochemical properties, a conclusion for the correlation with the biological response it is yet to be found. Hence, a special focus on the most desirable properties for an appropriate biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(70 citation statements)
references
References 115 publications
(210 reference statements)
2
66
0
2
Order By: Relevance
“…The biological responses of hydroxyapatites and their effectiveness as drug delivery systems are highly dependent on their physicochemical properties, such as their crystal shape, size, morphology and functional groups [ 8 ]. The key to understanding and predicting physicochemical and biological properties of nanocrystalline hydroxyapatites lies in the composition of their hydrated surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…The biological responses of hydroxyapatites and their effectiveness as drug delivery systems are highly dependent on their physicochemical properties, such as their crystal shape, size, morphology and functional groups [ 8 ]. The key to understanding and predicting physicochemical and biological properties of nanocrystalline hydroxyapatites lies in the composition of their hydrated surface layer.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the bone components, HA has been applied in biomaterial science and tissue engineering due to its biocompatibility and potential medical therapeutic avenues, whereas it is still necessary to understand how HA nanoparticles interact with a biological environment (cell, tissue, organ, or system). And it is important that they will not be just thought of as a structure that will be accumulated, internalized, or used to deliver a cargo, but a construct that will directly or indirectly modulate cell signaling pathways to improve or worsen a specific function, through the cell/HA functional groups contained in both [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the bioceramics which rapidly stimulate osteointegration and bone tissue generation are those that imitate the composition and structure of the bone mineral. In this regard, it has been demonstrated that ceramic biomaterials produced from HA nanoparticles show an improved resorbability and enhanced bioactivity than ceramics of micrometre range size [11,12]. The liberation of calcium ions from HA nanoparticles is comparable to that from apatite of biological origin and integrates more rapidly with tissues than that from rough crystals.…”
Section: Introductionmentioning
confidence: 99%